Pengolahan Limbah Cair Pencucian Kendaraan (dosmering) menggunakan Media Batang Pisang: (Studi Kasus Pencucian Mobil di Kecamatan Kadia, Kota Kendari, Sulawesi Tenggara) - Irmawati, Irmawati; Assiddieq, Moch.; Rosdiana, Rosdiana (Universitas Muhammadiyah Kendari, 2025)
Vehicle washing waste contains high levels of organic matter, so if disposed of directly, it can pollute and damage the environment. This study aims to determine the effectiveness of banana stems as an adsorption and filtration medium in reducing the levels of Total Suspended Solids (TSS) and Chemical Oxygen Demand (COD) in vehicle washing wastewater (dosmering) in Wowawanggu Village, Kadia District, Kendari City. The method used two treatments, namely the use of banana stems as a single medium and a mixed medium consisting of banana stems, fine sand, and gravel. Wastewater samples were taken from vehicle washing businesses, then tested for TSS and COD levels before and after treatment. The results showed that banana stems as a single medium were able to reduce TSS levels by 5.56% and COD by 7.56%, while the mixed medium reduced TSS by 77.78% and COD by 33.67%. Banana stems have the potential to be an effective and environmentally friendly natural material in liquid waste treatment.